Complexos de metais de transição multifuncionais para o tratamento e diagnóstico da doença de Alzheimer - Silva, Débora Eduarda Soares (Universidade Federal de São Carlos, 2016)
This work describes the synthesis and characterization of complexes cis-[Ru (phen)2(L)2]2+, where phen = 1,10-phenanthroline; L = 3,4-diaminopyridine and 4-aminopyridine, as well results for in vitro AD diagnosis and treatment. The complexes are soluble and stable in aqueous solution, display absorption (max = 480 nm;  = 9500 mol-1 L cm-1) and emission (em = 650 nm;  = 129 ns, 1.3 ns) in the region visible, and Stokes shift about 5000 cm-1. The luminescence of the complexes was incorporated into the cytoplasm of Neuro 2a cells, and showed no apparent damage of cell membrane integrity, morphology, and cytoxicity (IC50 >> 50 M). The inhibitory activity of complexes was evaluated for human recombinant acetylcholinesterase (hAChE) and butyrylcholinesterase from human serum (hBuChE) using the spectrophotometric method proposed by Ellman. The complexes are 4-fold more potent to hAChE than hBuChE, and the Lineweaver-Burk analysis indicated a reversible and mixed-type inhibition for both complexes. The antioxidant capacity of complexes was evaluated from the analysis of hydroxyl radical scavenging, and using the stable radicals 2,2- diphenil-1-picrylhydrazyl (DPPH•) and the 2,2-azinobis-3ethylbenzothiazoline- 6-sulphonate (ABTS•+). The complex cis-[Ru(phen)2(3,4-Apy)2]2+ showed a great antioxidant ability against the tested radicals. We used the luminescence of complexes to monitor in real time the self-aggregation of A with the FLIM technique. Under the same experimental conditions, the complexes bind to A1- 40 and to central hydrophobic core A15-21, but not to A22-35, that lacks the apolar Val18 and Phe20 residues, this indicates that the complexes can recognize and align specific sites of the A peptide.
Multifunctional transition metal complexes to treatment and diagnosis of Alzheimer´s disease
Keywords: Química inorgânica; Complexos de rutênio; Aminopiridinas; Doença de Alzheimer; Betaamilóide; CIENCIAS EXATAS E DA TERRA::QUIMICA